Features of Kazakh traditional music as a part of modern art market - Ospanova, Aigerim; Jumaniyazova, Raushan (Opción, 2019)
This article considers the problems of the modern art industry in Kazakhstan, especially the problems related to traditional Kazakh music. The authors in this article applied questionnaire as the main tool of the survey and the method of empirical research. In result, nearly all participants of the art market of traditional music experience difficulties in their professional activities. In conclusion, the music industry in Kazakhstan and around the world is rapidly changing, traditional market players are either developing at the same pace or disappearing, and new sales outlets, marketing methods and business models appear every day